Entre habitabilité et accessibilité au Bois de la Cambre - Nicola da Schio; Claire Pelgrims; Anneloes Vandenbroucke; Sebastiano Cincinnato (Brussels Studies)
We explore the tensions that exist between geographical accessibility and urban liveability in Brussels, by examining the case of the Bois de la Cambre, as a place of leisure as well as transiting. First, we study the park’s 150 years of history. Second, we present an explorative survey into citizens’ preferences for the park’s set-up in relation to the presence of motorized traffic. The research reveals a strong relation between the preferred set-up and the personal way of life. Through history, the set-up of the park has reflected broader societal changes in the way people organized their life, more than it reflected an explicit urban project. Today, the priority different social groups express for the setup of the park, reflects their residential location, mode of transport, and use of and access to green spaces. In this context, the study stresses the need to work as much on the construction of concrete mobility alternatives than on the construction of new urban and mobility imaginaries.